ChemInform Abstract: Intramolecular Palladium‐Catalyzed Alkene Carboalkynylation. Issue 51 (December 2015) - Nicolai, Stefano; Swallow, Peter; Waser, Jerome
Abstract: Triisopropylsilylethynyl bromide reacts with alkene‐tethered activated carbonyl compounds, thus allowing for the formation of five‐membered carbocycles in high yields and six‐membered carbocycles in moderate yields, albeit with low diastereoselectivities.